DESENTRALISASI INDONESIA MEMUPUK DEMOKRASI DAN PENCIPTAAN TATA PEMERINTAHAN LOKAL - Rudy Rudy (Fiat Justisia: Jurnal Ilmu Hukum, 2007)
Local Governance Decentralization covers the distribution of authority from the center to the regions in the form of deconcentration of authority and delegation of authority. Translation of decentralization set out in Law No. 22 of 1999 which is then converted into Law No. 32 of 2004 and Law No. 25 of 1999 which is then converted into Law No. 33 of 2004 on Financial Balance between the Central Government and Local Government in terms of implementation, both the regulation has not been fully implemented. Keywords: Democracy, Decentralization, Local Governance